The Influence Of Financial Literacy, Locus Of Control And E-Money On Consumptive Behavior Of Generation Z In Mojokerto District - Siti Muclisi Rohma Nurfarida; Nersiwad Nersiwad; Rini Armin (International Journal of Management and Business Economics, 2023)
Everyone must have a need to survive. However, an option if irrational needs make us interested in consuming something excessively, and make us fall into the category of consumptive people. Generation Z is said to be the generation of the internet which is always updated and keeps abreast of developments regarding fashion trends circulating in the internet world which has indirectly carried out consumptive behavior. This study aims to determine the extent to which financial literacy, locus of control and e-money influence the consumptive behavior of Generation Z in Mojokerto Regency. The research method used in this research is quantitative with descriptive statistical analysis based on primary data obtained from questionnaires, and secondary data obtained from books, official websites, journals etc. This research was conducted by distributing questionnaires (online) to respondents. The population in this study is generation Z, aged 20-24 years, the number of samples determined is 100 people using purposive sampling technique. The results of the study show that simultaneously financial literacy, locus of control and e-money have a significant effect on consumptive behavior in Generation Z in Mojokerto Regency. Partially, financial literacy has no significant effect on the consumptive behavior of Generation Z in Mojokerto Regency. Partially, locus of control has a significant influence on the consumptive behavior of Generation Z in Mojokerto Regency. Partially, E-money has no significant effect on the consumptive behavior of Generation Z in Mojokerto Regency.